Corrigendum to “Characterising dark net marketplace purchasers in a sample of regular psychostimulant users” [International Journal of Drug Policy 35 (2016) 32–37]((S0955395916000335)(10.1016/j.drugpo.2016.01.010)) - Van Buskirk, J.; Roxburgh, A.; Bruno, R.; Naicker, S.; Lenton, Simon; Sutherland, R.; Whittaker, E.; Sindicich, N.; Matthews, A.; Butler, K.; Burns, L. (Elsevier BV, 2017)
The authors regret that there is an inconsistency between figures presented in the abstract and those reported in the text of the manuscript. Specifically, the abstract states that 68 out of 800 participants in the sample reported recent darknet use, while the manuscript states that 66 of the 745 participants reported recent darknet use. The latter numbers are correct for the analyses performed, that is, 66 of the 745 interviewed participants had purchased from the darknet in the preceding 12 months, and comprise the sample included in the regression model. While the former numbers are correct for the entire sample of recruited participants, they are not appropriate for the analyses performed. The authors would like to apologise for any inconvenience caused.